Low Back Pain and Obesity (Review Article) - Al- Edanni, Mohammed Sh.; Al- Edanni, Mohammed Sh. (AL-Kindy College Medical Journal, 2019)
Low back pain a major causes of morbidity throughout the world and it is a most debilitating condition ,and can lead to decreased physical function ,compromised quality of life, and psychological distress.Obesity is nowadays a pandemic condition. Obese subjects are commonly characterized by musculoskeletal disorders and particularly by non-specific LBP. However, the relationship between obesity and LBP remain to date unsupported by objective measurements of mechanical behavior of spine and it is morphology in obese subjects.                                    Key words: obesity, low back pain,